2020
DOI: 10.1007/s11661-020-06036-0
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ Monitoring for Defect Identification in Nickel Alloy Complex Geometries Fabricated by L-PBF Additive Manufacturing

Abstract: Published literature shows defect formation during laser powder bed fusion additive manufacturing (AM) of nickel base superalloys are sensitive to alloy chemistry, processing conditions, and geometry. In this work, ability to detect spatial distributions of defects is explored using in-situ monitoring of thermal signatures and surfaces. Simple and complex geometrical components were fabricated with CM247-LCÒ powder in an AM machine outfitted with optical and thermal sensors. The spatial and temporal variations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 44 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, the porosity analysis was performed using cubes, while the creep specimen were cylinders. Some studies on Electron Beam Powder Bed Fusion of various metals have found that the sample geometry affects the porosity (Frederick et al 2018;McNeil et al 2020), pore location (Yoder et al 2019) and mechanical properties (Yoder et al 2018). However, these studies compared simple (e.g.…”
Section: Effect On Densitymentioning
confidence: 99%
“…Furthermore, the porosity analysis was performed using cubes, while the creep specimen were cylinders. Some studies on Electron Beam Powder Bed Fusion of various metals have found that the sample geometry affects the porosity (Frederick et al 2018;McNeil et al 2020), pore location (Yoder et al 2019) and mechanical properties (Yoder et al 2018). However, these studies compared simple (e.g.…”
Section: Effect On Densitymentioning
confidence: 99%
“…The ability to scan objects in 3D without slicing or sectioning is the biggest advantage of X-ray CT over other microscopy techniques, such as scanning electron microscopy, transmission electron microscopy and optical microscopy. X-ray CT has been used to study various 3D printed materials in terms of size, spatial distribution and the morphology of defects [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Moreover, recent advances have substantially supported the use of various wire materials such as aluminum, [16][17][18] titanium, [19][20][21] and nickel alloys. [22][23][24][25] However, the path generation in the arc-based metal AM is still based on a point-by-point or layer-by-layer manufacturing approach. [26][27][28] Thus, their print speed is limited by stepwise material deposition due to the time of solidification and cooling of molten metals during the printing process.…”
Section: Introductionmentioning
confidence: 99%